Inclusion on Purpose : an intersectional approach to creating a culture of belonging at work - Tulshyan, Ruchika (Cambridge, Massachusetts : The MIT Press, 2022)
"A guide for organizations to improve their diversity, equity, and inclusion efforts, focusing specifically on the experiences of women of color"--
Includes bibliographical references and index.
Keywords: Diversity in the workplace -- Case studies; Minority women -- Employment; Women's rights